Pengaplikasian Mikrokontroler Arduino Uno Pada Simulasi Sistem Pengapian Mesin Bensin 4 Langkah (4 Silinder) - Anggi Septiawan Putra; Nusyirwan Nusyirwan; Maimuzar Maimuzar (Jurnal Teknik Mesin, 2017)
The 4 stroke (4 cylinder) gasoline engine ignition system simulation based on the Arduino Uno microcontroller was designed as one of the modeling of conventional ignition system modification into an electronic ignition system based on the Arduino Uno microcontroller. Conventional ignition systems are modified by removing distributor components and replaced with microcontrollers as ignition system controllers. Spark plug and coil cables are replaced with Igniton coil that uses Igniter. Arduino Uno microcontroller is used as a controller that receives signals from the optocoupler sensor and activates the module relay so that the electric current enters the Ignition Trigger, the voltage needed by Igniton Trigger is 2 V by using a step down transformer to reduce the voltage. So that the Ignition Coil is active and produces a high voltage so that it can produce sparks on each spark plug. This Arduino Uno microcontroller processes data received from an optocoupler sensor